2016
DOI: 10.1073/pnas.1503252113
|View full text |Cite
|
Sign up to set email alerts
|

Neural basis of reward anticipation and its genetic determinants

Abstract: Dysfunctional reward processing is implicated in various mental disorders, including attention deficit hyperactivity disorder (ADHD) and addictions. Such impairments might involve different components of the reward process, including brain activity during reward anticipation. We examined brain nodes engaged by reward anticipation in 1,544 adolescents and identified a network containing a core striatal node and cortical nodes facilitating outcome prediction and response preparation. Distinct nodes and functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 52 publications
3
48
0
Order By: Relevance
“…Furthermore, this working hypothesis might explain the specific cFos expression found in the cerebellum of rodents expressing a preference for a cocaine-paired odor cue that was not observed when the animal did not acquire this conditioned response (Carbo-Gas et al, 2014ab). A recent neuroimaging study that monitored brain activity during reward anticipation showed 4 active nodes encompassing broad cerebellar areas including the vermis (Jia et al, 2016). Nevertheless, the authors of the study did not propose a specific hypothesis for the cerebellar activity, as no correlation with performance in neuropsychological tests was found.…”
Section: The Cerebellum's Role: Craving or Prediction?mentioning
confidence: 90%
“…Furthermore, this working hypothesis might explain the specific cFos expression found in the cerebellum of rodents expressing a preference for a cocaine-paired odor cue that was not observed when the animal did not acquire this conditioned response (Carbo-Gas et al, 2014ab). A recent neuroimaging study that monitored brain activity during reward anticipation showed 4 active nodes encompassing broad cerebellar areas including the vermis (Jia et al, 2016). Nevertheless, the authors of the study did not propose a specific hypothesis for the cerebellar activity, as no correlation with performance in neuropsychological tests was found.…”
Section: The Cerebellum's Role: Craving or Prediction?mentioning
confidence: 90%
“…Reward anticipation neural networks involve both the striatum and cortical regions including visual association cortex and the somatosensory cortex and the fact that Gpr88 −/− mice did not anticipate the water access suggests a possible alteration of this neural network. This is consistent with the prominent expression of GPR88 in both striatum and cortex .…”
Section: Discussionmentioning
confidence: 99%
“…This interpretation is based on the fact that, although the 24 hours water deprivation step does not produce robust physiological changes, 35 mice are subjected to 19-hour water deprivation for 9 consecutive days and that, under these conditions, drinking water is considered an innately rewarding behavior. 36 Reward anticipation neural networks involve both the striatum and cortical regions including visual association cortex and the somatosensory cortex 37 and the fact that Gpr88 −/− mice did not anticipate the water access suggests a possible alteration of this neural network. This is consistent with the prominent expression of GPR88 in both striatum and cortex.…”
Section: The Intellicage System Shows Delayed Anticipatory Behaviormentioning
confidence: 99%
“…Furthermore, adolescents at a more advanced pubertal stage exhibited less striatal and more medial prefrontal cortex (mPFC) activation during reward processing than those at a less advanced pubertal stage (Forbes et al, 2010). Typically, the effects of gender and puberty have not been analyzed or have been controlled for statistically in previous reward processing studies (Bjork et al, 2004(Bjork et al, , 2010Jia et al, 2016;Peters et al, 2011;Stringaris et al, 2015), which make their specific contribution in reward processing unclear. Typically, the effects of gender and puberty have not been analyzed or have been controlled for statistically in previous reward processing studies (Bjork et al, 2004(Bjork et al, , 2010Jia et al, 2016;Peters et al, 2011;Stringaris et al, 2015), which make their specific contribution in reward processing unclear.…”
Section: Introductionmentioning
confidence: 99%